Evaluation of the residual prestress force in aged railway concrete sleepers considered for reuse - Seketema, Nonofo Olefile (Department of Civil Engineering, 2026)
The increasing demand for railway transport in South Africa has led to the expansion and upgrade of the existing track infrastructure in recent years. Given the high costs associated with new development or refurbishment of existing infrastructure, asset owners and managers are faced with the challenge of optimising expenditures while extending the service life of their infrastructure. One of the essential structural components of a conventional railway track is the prestressed concrete sleeper. In South Africa, these sleepers are designed to last for 40 years, and their replacement plan is aligned with their design life. Given the desire to extend the useful life of sleepers, aged concrete sleepers are often removed from primary running lines for second-hand use in branch, sidings and yard lines. However, the current quality assurance system for reusing sleepers relies mainly on visual condition assessments, which only consider the external surface of the concrete, neglecting the internal condition of the reinforcing and prestress steel and, critically, the remaining prestress force, which is crucial for the flexural strength. To address this gap, a study was conducted to determine the prestressing force of concrete sleepers post-design life using the dynamic relaxation method. The study involved sampling 21 P2 concrete sleepers, comprising eighteen old sleepers (manufactured in 1977) and three new sleepers (manufactured in 2006). Six of the 21 sleepers were used to determine compressive and tensile strength values of concrete and steel wires, respectively, while the remaining 15 sleepers were subjected to dynamic relaxation testing. Visual condition assessment revealed several types of concrete damage caused by operation and maintenance activities, with notable bending cracks propagating from the sleeper base around the rail seat region. Additionally, concrete surface abrasion was identified on the base, sleeper sides, and on the rail seat area. The two steel components, wires and cast-iron, extracted from the concrete were found to have corroded to varying degrees. The results of the dynamic relaxation method demonstrated significant reduction of the prestress force in both aged and new sleepers when compared to the requirements of the BBG8755 specification. The mean loss of prestress force was 77% and 65% for old and new sleepers, respectively. Whilst prestress loss was expected for aged sleepers, the high loss for new sleepers was unexpected. Further testing is therefore recommended to identify contributing factors and verify the results through expanded testing. The prestress force loss over the useful life of concrete sleepers confirmed the need for a robust second-hand sleeper classification system. The proposed guideline for evaluating reusable prestressed concrete sleepers incorporates both visual condition assessment and the concrete and steel materials strength and durability confirmation tests.